1991
DOI: 10.1111/j.1476-5381.1991.tb09844.x
|View full text |Cite
|
Sign up to set email alerts
|

Excretion of metabolites of prostacyclin and thromboxane by rats with nephrotoxic nephritis: effects of interleukin‐1

Abstract: 1 To obtain direct evidence of abnormal eicosanoid biosynthesis in rats injected with anti-glomerularbasement-membrane antibodies (a-GBM), products derived from thromboxane A2 (TXA2) and prostacyclin (PGO2) were measured in 24 h urine collections before and after a-GBM. 2 Administration of a-GBM (9.5 mg) caused albuminuria, decreased creatinine clearance, increased numbers of intra-glomerular neutrophils and increased excretion of TXB2, 2,3-dinor-TXB2 (products of TXA2) and 6-oxo-PGF1a and 2,3-dinor-6-oxo-PGF1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1992
1992
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Quantification of urinary PGE metabolites [108] and the major urinary metabolite of PGI [109] can potentially be another biomarker for fatty acid status. In 1988, Kivits et al reported that in rats, an AA diet increased urinary tetranor-prostaglandin E 1 (PGE-M) which is the major urinary metabolite of PGE 2 [110].…”
Section: Prostaglandin 3-series As Biomarkers For Epa Statusmentioning
confidence: 99%
“…Quantification of urinary PGE metabolites [108] and the major urinary metabolite of PGI [109] can potentially be another biomarker for fatty acid status. In 1988, Kivits et al reported that in rats, an AA diet increased urinary tetranor-prostaglandin E 1 (PGE-M) which is the major urinary metabolite of PGE 2 [110].…”
Section: Prostaglandin 3-series As Biomarkers For Epa Statusmentioning
confidence: 99%
“…They increase urinary volume and sodium excretion transiently. These changes are independent of changes in glomerular filtration rate, effective renal plasma flow [35] or thromboxane excretion [36]. However, they correlate with increased urinary prostaglandin excretion [35].…”
Section: Discussionmentioning
confidence: 92%
“…We have shown previously that systemic injection of IL-l/f in this model increased renal synthesis of prostaglandin E; and prostaglandin-1;. and ibuprofen decreased both prostaglandin synthesis and increased albuminuria [36]; there were no changes in Ihromboxanc excretion in these sUidies.…”
Section: Discussionmentioning
confidence: 96%
“…The major urinary metabolites of AA-derived 6-keto-PGF 1 ␣ have been described in both man ( 12,17,18 ) and rats ( 19 ) but not in mice. In contrast, no careful, quantitative analysis of the metabolites of PGI 3 have been performed in any species, although homologs of the major PGI 2 metabolites have been measured in urine of primates following dietary fi sh oil (20)(21)(22).…”
Section: Synthesis Of 1919202020-d5 Methyl 5z8z11z14z 17z-eicmentioning
confidence: 99%